Portable grease trap for wastewater management system: A conceptual design approach - Hussin M.S.F.; Shamsuddin M.A.; Jumaidin R.; Zakaria A.A.; Jenal N. (Penerbit Akademia Baru, 2023)
Irresponsible human attitude towards food waste management has led to water pollution all over the places especially in the public sewers. The abundance of small solid particles like fat, oil and grease (FOG) can still pass through the sink filter during daily dishwashing, which might cause clogging of the piping system. This research aimed to develop a conceptual design of a passive grease trap for wastewater management system. The process of determining the best design was done through customer survey, house of quality, morphological chart, and pugh method. The final concept has a reasonable size of 300 mm 430 mm 300 mm, a mass of approximately 7 kg that can be considered as light and portable. The grease trap system is divided into 3 partitions. The first partition functions as a solid filter. The second partition functions as oil filter as water is denser than oil. The last partition function as depositing remaining waste prior to the entry of water into public sewer. The proposed design is economical since the material used is only PVC and mild steel. 2018 Penerbit Akademia Baru.